Nano Online 2016
DOI: 10.1515/nano.12951_2015.44
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity and biocompatibility of ceragenin-coated magnetic nanoparticles

Abstract: Background: Ceragenins, synthetic mimics of endogenous antibacterial peptides, are promising candidate antimicrobial agents. However, in some settings their strong bactericidal activity is associated with toxicity towards host cells. To modulate ceragenin CSA-13 antibacterial activity and biocompatibility, CSA-13-coated magnetic nanoparticles (MNP-CSA-13) were synthesized. Transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC) and thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…The amines in ceragenins reversibly form Schiff bases (imines), which allow the nanoparticles to aggregate ceragenins [103]. Hayes et al [101] prepared silver nanoparticles coated with CSA-124 and found that they were five times more bactericidal than silver alone, with MICs against S. aureus and E. coli of ca.…”
Section: Ceragenins On Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The amines in ceragenins reversibly form Schiff bases (imines), which allow the nanoparticles to aggregate ceragenins [103]. Hayes et al [101] prepared silver nanoparticles coated with CSA-124 and found that they were five times more bactericidal than silver alone, with MICs against S. aureus and E. coli of ca.…”
Section: Ceragenins On Nanoparticlesmentioning
confidence: 99%
“…12 and 24 ppm respectively. Bucki et al [103] showed that ceragenin-coated, magnetic nanoparticles retained potent bactericidal activity. In addition, sequestering ceragenins on nanoparticles enhanced biocompatibility.…”
Section: Ceragenins On Nanoparticlesmentioning
confidence: 99%
“…16 Additionally, ceragenin CSA-13-coated MNPs (MNP-CSA-13) exhibited strong antibacterial activity and the ability to prevent bacterial biofilm formation in different body fluids, with a significant decrease in its hemolytic activity when the molecule was immobilized on the nanoparticle surface. 17 In contrast, it has been reported that iron-containing nanoparticles may influence the ability of bacteria to absorb iron for growth, increase virulence, and inhibit AMP function. 18 Here, we present the intrinsic antifungal activity of the citric acid-coated MnFe 2 O 4 -NPs and the improvement of their antifungal activity when these nanoparticles were conjugated with a 12 aa peptide named Cm-p5.…”
mentioning
confidence: 99%
“…19,20 Studies show that the immobilization/encapsulation process improves the overall biological effectiveness of active agents including pharmacokinetic parameters (bioavailability, clearance) and reduces the side effects. [21][22][23] In addition, it has been noted that the antibiotic resistance of drug-resistant pathogens may be overcome by using nanoparticles as antibiotic carriers. 24 Among the many types of nanostructures, core-shell magnetic iron oxide nanoparticles are the most commonly used drug carriers in biomedical studies.…”
mentioning
confidence: 99%
“…Our previous studies indicate that the immobilization of ceragenin on the MNP surface increases its antibacterial activity in the presence of body fluids. 22 In addition, recent work suggests that the application of nanosystems composed of MNPs and polyene antibiotic may be used for the treatment of infections caused by polyeneresistant fungal strain. 29 In the present study, we evaluate the activity of magnetic nanosystems functionalized with chlorhexidine against clinical isolates of pathogens from different groups including representatives of Gram-positive and Gram-negative bacteria and fungal cells.…”
mentioning
confidence: 99%